Family agriculture of Itabaiana/SE from the agricultural census (2017) - Carvalho, Diana Mendonça de; Costa, José Eloízio da (Geografares, 2022)
The article on screen performs a geographic reading of the socioeconomic characteristics of family farming in the municipality of Itabaiana/SE, through the 2017 Agricultural Census (IBGE, 2019). To this end, bibliographical research and analysis of indicators were carried out, starting from 1) the domain of family farming among the numbers of agricultural establishments; 2) profile of family actors; 3) schooling rate; 4) offer ATER; 5) minimal socioeconomic organization; and 6) low access to bank credit. Given these data, the family segment of the municipality stands out in the production of temporary crops and livestock, in addition to contributing to the proliferation of vehicles in the countryside, such as the use of motorcycles. Even so, family farming in the municipality of Itabaiana presents problems regarding the need for public policies to support its production base, while it responds to a considerable demand for vegetables from the municipality and other micro-regions, placing Itabaiana within the universe of agricultural marketing.